2014
DOI: 10.1645/13-359.1
|View full text |Cite
|
Sign up to set email alerts
|

Racing Pigeons: A Reservoir for Nitro-Imidazole–ResistantTrichomonas gallinae

Abstract: Trichomonas gallinae , the cause of avian trichomonosis, is most commonly found in the order Columbiformes. Racing pigeons are often treated preventively with nitro-imidazoles, which could result in the emergence of resistant isolates, and these isolates can be a threat to wildlife when exchanges occur. The sequence type of 16 T. gallinae isolates obtained from racing pigeons and 15 isolates from wild pigeons was determined based on the ITS1/5.8S rRNA/ITS2 region sequence. In addition, the resistance profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…To assess MTZ resistance in T. gallinae strains (Rouffaer et al, 2014), a 24-h MIC breakpoint (15.6 μg/mL) was established. Our study revealed that the 24 h MIC of MTZ was 50 μg/mL, which differs significantly from that reported by Rouffaer et al, whose specified value differs.…”
Section: Discussionmentioning
confidence: 99%
“…To assess MTZ resistance in T. gallinae strains (Rouffaer et al, 2014), a 24-h MIC breakpoint (15.6 μg/mL) was established. Our study revealed that the 24 h MIC of MTZ was 50 μg/mL, which differs significantly from that reported by Rouffaer et al, whose specified value differs.…”
Section: Discussionmentioning
confidence: 99%
“…2 In our series, only 4 of 24 cases of PiHV-infected adult pigeons had the typical gross lesions of trichomonosis. The presence of immunosuppressive agents (such as PiCV) or nitroimidazole resistance 28 may have facilitated the pathogenicity of this protozoal agent in these birds.…”
Section: Discussionmentioning
confidence: 99%
“…The main reservoirs are Columbiformes, but many avian species, including domestic and wild birds, can be infected (1). Nitroimidazoles are the drugs of choice for treatment, but several studies reported resistant strains, both, in vivo (2)(3)(4)(5) and in vitro (3,4,(6)(7)(8). Since the ban of the use of nitroimidazoles for prevention in the EU and the USA, there is no alternative to prevent the disease (9).…”
Section: Introductionmentioning
confidence: 99%